The Illusion of Risk Control What Does it Take to Live With Uncertainty? - Motet, Gilles; Bieder, Corinne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY 4.0 license.
1 Uncertainty: new perspectives, questions and proposals, by Gilles Motet -- 2 Uncertainty - its ontological status and relation to safety, by Ove Njå, Øivind Solberg & Geir Sverre Braut -- 3 A conceptual foundation for assessing and managing risk, surprises and black swans, by Terje Aven -- 4 Recognizing complexity in risk management: the challenge of the Improbable, by Jean Pariès -- 5 Promoting safety by increasing uncertainty - Implications for risk Management, by Gudela Grote -- 6 Practices in the danger culture of late industrial society, by Arie Rip -- 7 Judicial Review of Uncertain Risks in Scientific Research, by Eric E. Johnson -- 8 What can Japan's early modern capital of Edo teach us about risk management?, by Jordan Sand -- 9 Conclusion, by Corinne Bieder.
Keywords: Security systems; Economic sociology; Social choice; Welfare economics; Industrial organization; Sustainability; Security Science and Technology; Economic Sociology; Social Choice and Welfare; Organization; Sustainability